Filsafat Pendidikan dalam Pemikiran Religius-Konservatif Syekh Nawawi al-Bantani dan Relevansinya terhadap Dunia Pendidikan Islam Kontemporer - Agung, Arnin; Maragustam, Maragustam; Usman, Usman (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study examines Shaykh Nawawi al-Bantani’s educational thought through library-based research using content and descriptive analysis. His ideas remain highly relevant to contemporary Islamic education, emphasizing four pillars: foundations based on the Qur’an and Sunnah, goals centered on the development of knowledgeable and virtuous Muslims, a balanced curriculum between religious and secular sciences, and a learning method rooted in ethics and systematic process. His holistic and integrative model aligns with national education policy and addresses challenges of globalization and secularization. This study highlights the continuing relevance of Shaykh Nawawi al-Bantani’s religious-conservative educational philosophy to contemporary Islamic education. By reconstructing his classical ideas into a contextual and integrative model, the research bridges traditional moral–spiritual values with modern educational demands. Rooted in Qur’anic principles, ethics, and adab, his thought offers a holistic framework that unites cognitive, affective, and spiritual dimensions of learning. The study thus contributes to the renewal of Islamic educational philosophy and provides a practical foundation for character formation within the modern national education system.